2015
DOI: 10.1055/s-0035-1555616
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal Augmentation in Rhinoplasty: A Survey and Review

Abstract: Understanding the nuanced practices and grafting options of dorsal augmentation will improve outcomes and results in rhinoplasty. To better understand the practices of dorsal augmentation among our colleagues. To review the current literature regarding the indications, safety profiles, and outcomes of different materials used in dorsal augmentation. A PubMed search was performed to capture current articles containing reviews or large series regarding the safety and efficacy of various grafting materials used f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 22 publications
(35 reference statements)
0
35
0
Order By: Relevance
“…Notwithstanding, online surveys have been effectively used in many scientific studies published in prominent journals and we believe that once pertinently structured, an online survey can provide results as valid and reliable as an in-person one. 13,14 In conclusion, it has been observed that patients are influenced by visual factors (the factors that they directly see with their eyes, such as simulation results, pre-and postoperative photographic result, and meeting a previously operated patient by the same surgeon) when deciding on a rhinoplasty procedure and find the surgical outcome of an experienced surgeon more appealing than a simulation. Also, there is an evident consciousness among potential rhinoplasty patients regarding the use of preoperative simulations which is likely to increase their demand in future, mandating more surgeons to use them.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding, online surveys have been effectively used in many scientific studies published in prominent journals and we believe that once pertinently structured, an online survey can provide results as valid and reliable as an in-person one. 13,14 In conclusion, it has been observed that patients are influenced by visual factors (the factors that they directly see with their eyes, such as simulation results, pre-and postoperative photographic result, and meeting a previously operated patient by the same surgeon) when deciding on a rhinoplasty procedure and find the surgical outcome of an experienced surgeon more appealing than a simulation. Also, there is an evident consciousness among potential rhinoplasty patients regarding the use of preoperative simulations which is likely to increase their demand in future, mandating more surgeons to use them.…”
Section: Discussionmentioning
confidence: 99%
“…Extrusion rates of silicone implants typically range from 2.1% to 3.7%. 3 Lam and Kim 25 used an L-shaped silicone implant to provide dorsal and tip augmentation. However, owing to the characteristics of silicone, the implant could appear to be unnatural and extruded if the columella portion of the implant was too pronounced.…”
Section: Discussionmentioning
confidence: 99%
“…One may argue that a rhinoplasty specialist may have a lower rate; however, it is difficult to truly assess, as patients often change surgeons or even go to different cities and different countries to have cosmetic surgeries performed. In Asian rhinoplasty, augmentation is a key part of the surgery, and implants are used almost exclusively in Asia, particularly for primaries [1][2][3][4][5]. Both silicone and Values are presented as number.…”
Section: Discussionmentioning
confidence: 99%
“…The augmentation rhinoplasty procedure has long been one of the most common cosmetic procedures in Asian populations [1][2][3], and silicone is the most widely used nasal augmentation material in Asia [2][3][4][5]. How-www.jcosmetmed.org ever, in the past few decades, expanded polytetrafluoroethylene expanded polytetrafluoroethylene (ePTFE, Gore-Tex ® ) has become more popular as an alternative implant [2][3][4][5]. Both implant materials have been used for decades in plastic and cardio-vascular surgery, and they both have excellent biocompatibility profiles.…”
Section: Introductionmentioning
confidence: 99%